Pengaruh Teknologi Modern Terhadap Moralitas Dan Tanggung Jawab Siswa Sekolah Dasar - Anisa Nurhasanah; Haldini Reygita; Salsa Nabila Marcella Kalalo (Student Scientific Creativity Journal, 2024)
The impact of the development of information technology today on various aspects of global life. Although modern technology provides great benefits, the article highlights the ethical and moral challenges faced, especially by children and adolescents. Technology influences the understanding of responsibility and ethics in social interactions, especially through social media and the use of digital devices. This article emphasizes the importance of education that focuses not only on knowledge transfer, but also on character building. In addition, the article underlines the need for moral and ethical education in line with technological developments, so that children are able to understand and apply social responsibility in an increasingly advanced digital era. Technology has the potential to provide positive benefits, but it can also have a negative impact on behavior and morale if not used wisely.